What drove the profitability of colonial firms? Labour coercion and trade preferences on the Sena Sugar Estates (1920-74) - Sam Jones; Peter Gibbon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The magnitude of returns to colonial-era investments in Africa has been addressed in an extensive literature, as have the nature and legacies of extractive colonial institutions. However, the link between these institutions and the profitability of firms remains unclear. We reconstruct the annual financial records of Sena Sugar Estates in Portuguese East Africa (today's Mozambique) over the period 1920-74 to probe the contributions of forced labour and preferential trade arrangements to the performance of the firm. We show that Sena Sugar Estates achieved stable and solid returns to capital, comparable in size to a range of domestic UK firms. Counterfactual simulations suggest that the firm's profitability was highly dependent on sustained access to cheap labour, but generally was not so dependent on trade preferences. At the same time, a production function analysis suggests that higher reliance on rents from forced labour was associated with lower total factor productivity at the Estates. This helps explain why extractive institutions did not translate into 'super-profits'.
Keywords: J24; N77; N87; 330; Mozambique; sugar; forced labour; trade preferences; colonial era